Branding Vocational High School Graduates with Unique Selling Proposition Strategy to Increase Job Absorption: School Website Context - Muhammad Nuruzzaman; Nanang Purniawan; Hanny Radifa Aulia; Min Hajul Abidin (Universitas Negeri Yogyakarta, 2024)
Background: Schools often brand themselves on websites as a means of virtual communication, but rarely brand their graduates there. When both the school and its graduates have been branded, the strategies often implemented are not in accordance with existing theory. The focus of this research is: (i) Have Vocational Schools provided branding to their graduates; (ii) What kind of branding has been carried out by SMK; (iii) What is the average percentage of branding carried out by schools in fulfilling the 5 USP domainsMethod: The research method used is quantitative, with the number of VHSs studied as many as 5 schools selected from 4 cities in the province of Yogyakarta Special Region which holds the title of VHS center of excellence. The instrument used is in the form of 5 USP domains and uses a Guttman measurement scaleResult: The results showed: (i) All schools have conducted branding of their graduates.; (ii) Branding carried out by the majority of VHSs is in the form of standard branding by explaining the competencies possessed by their graduates very briefly and less comprehensively; (iii) Of the 5 VHSs studied, the average school obtained 55.54%, which indicates that the branding carried out by VHSs so far is still not optimal and needs to be improvedConclusion: This research has an impact on vocational school managers to design branding that best suits the characteristics of their school. The branding displayed on the school website must be original, attractive, and convincing to the graduate user industry